Large-scale water quality prediction using federated sensing and learning: A case study with real-world sensing big-data - Park, Soohyun; Jung, Soyi; Lee, Haemin; Kim, Joongheon; Kim, Jae Hyun (Sensors, 2021)
Green tide, which is a serious water pollution problem, is caused by the complex relationships of various factors, such as flow rate, several water quality indicators, and weather. Because the existing methods are not suitable for identifying these relationships and making accurate predictions, a new system and algorithm is required to predict the green tide phenomenon and also minimize the related damage before the green tide occurs. For this purpose, we consider a new network model using smart sensor-based federated learning which is able to use distributed observation data with geologically separated local models. Moreover, we design an optimal scheduler which is beneficial to use real-time big data arrivals to make the overall network system efficient. The proposed scheduling algorithm is effective in terms of (1) data usage and (2) the performance of green tide occurrence prediction models. The advantages of the proposed algorithm is verified via data-intensive experiments with real water quality big-data.
Keywords: Accurate prediction; Complex relationships; Network modeling; Optimal scheduler; Pollution problems; Prediction model; Water quality indicators; Water quality predictions; Big data; Federated learning; Optimization; Scheduling; Smart IoT sensor